Annual Report 2013/Japan Internacional Research center for Agricultural Sciences - Japan Internacional Research center for Agricultural Sciences (Japon: Editorial Board, 2014)
Trata de un reporte anual.
1.ResearchOverview 2.Training and Invitation Program 3. Appendix
incluye índice
Col. Agro
Keywords: 1.ENVIRONMENT AND NATURAL RESOURCE MANAGEMENT 2.RURAL LIVELIHOOD 3.JIRCAS